Brightness through Local Constraint—LNA‐Enhanced FIT Hybridization Probes for In Vivo Ribonucleotide Particle Tracking1. Issue 42 (28th August 2014) - Hövelmann, Felix; Gaspar, Imre; Loibl, Simon; Ermilov, Eugeny A.; Röder, Beate; Wengel, Jesper; Ephrussi, Anne; Seitz, Oliver
Abstract Imaging the dynamics of RNA in living cells is usually performed by means of transgenic approaches that require modification of RNA targets and cells. Fluorogenic hybridization probes would also allow the analysis of wild‐type organisms. We developed nuclease‐resistant DNA forced intercalation (FIT) probes that combine the high enhancement of fluorescence upon hybridization with the high brightness required to allow tracking of individual ribonucleotide particles (RNPs). In our design, a single thiazole orange (TO) intercalator dye is linked as a nucleobase surrogate and an adjacent locked nucleic acid (LNA) unit serves to introduce a local constraint. This closes fluorescence decay channels and thereby increases the brightness of the probe–target duplexes. As few as two probes were sufficient to enable the tracking of oskar mRNPs in wild‐type living Drosophila melanogaster oocytes.